Socialization Of The Code Of Conducttennis Junior Tournament For The Parents And The Coach Of The Junior Tennis Athletes In Sumatera - Rices Jatra (Jurnal Berkarya Pengabdian Masyarakat, 2019)
This activity aims to provide Knowledge on the Rules of National Junior Tennis Matching for Parents and Trainers of Junior Tennis Athletes in Sumatra, so that parents and coaches are able to understand the rules of the Junior Tennis Match so that they can provide knowledge and train their students to compete Written procedures arranged by PP PELTI for the TDP National Junior Championship (PELTI Recognized Tournament). This refers to the ITF (International Tennis Federation) regulations so that coaches and parents are easy to educate and train their children to play in accordance with the Ordered Rules that have been arranged. The activity included Socialization Of The Code Of Conduct Tennis Junior Tournament For The Parents And The Coach Of The Junior Tennis Athletes In Sumatera".This activity was held on April 6, 2019 in Kecamatan Kubung, Kabupaten Solok, West Sumatra. The activity was attended by 30 coaches and parents of athletes who competed in the national tennis championship at the Solok II Regent Cup in 2019.